2014
DOI: 10.1038/ncomms6822
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility in thin films formed via supersonic impact deposition of nanocrystals synthesized in nonthermal plasmas

Abstract: Thin films comprising semiconductor nanocrystals are emerging for applications in electronic and optoelectronic devices including light emitting diodes and solar cells. Achieving high charge carrier mobility in these films requires the identification and elimination of electronic traps on the nanocrystal surfaces. Herein, we show that in films comprising ZnO nanocrystals, an electron acceptor trap related to the presence of OH on the surface limits the conductivity. ZnO nanocrystal films were synthesized using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(154 citation statements)
references
References 34 publications
7
147
0
Order By: Relevance
“…It has been demonstrated that the ALD of Al 2 O 3 is an effective means to passivate defects in films formed by semiconductor NCs such as ZnO NCs, PbSe NCs, PbS NCs, and CdSe NCs . When the Ge‐NC films are treated with the ALD of Al 2 O 3 , the electrical conductivity of the Ge‐NC films increases across all doping levels (Figure a–e).…”
Section: Resultsmentioning
confidence: 98%
“…It has been demonstrated that the ALD of Al 2 O 3 is an effective means to passivate defects in films formed by semiconductor NCs such as ZnO NCs, PbSe NCs, PbS NCs, and CdSe NCs . When the Ge‐NC films are treated with the ALD of Al 2 O 3 , the electrical conductivity of the Ge‐NC films increases across all doping levels (Figure a–e).…”
Section: Resultsmentioning
confidence: 98%
“…However, these techniques suffer from numerous disadvantages including complex and time consuming steps, high temperatures, inert atmosphere, expensive source materials, toxic organic solvents, and surfactants . Furthermore, the control of the resulting morphology, crystallinity, and agglomeration of the nanostructures is a significant challenge which demands additional cleaning steps to remove undesired by‐products and chemical impurities or residues . The presence of surfactant or ligand chemistries is essential for minimizing particle coalescence and agglomeration during standard colloid synthesis; however, such chemistries impact significantly on the resultant nanoparticle optoelectronic properties and restrict the opportunity for bandgap tuning .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the control of the resulting morphology, crystallinity, and agglomeration of the nanostructures is a significant challenge which demands additional cleaning steps to remove undesired by‐products and chemical impurities or residues . The presence of surfactant or ligand chemistries is essential for minimizing particle coalescence and agglomeration during standard colloid synthesis; however, such chemistries impact significantly on the resultant nanoparticle optoelectronic properties and restrict the opportunity for bandgap tuning . Synthesis of non‐agglomerated and pure CuO nanostructures is imperative for their successful integration in application devices, and therefore, developing an alternative, cheap, and environmentally friendly synthesis method is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguing combinations of one materials for the nanocrystal phase with another material for the matrix phase can be envisioned. One example was recently presented by Thimsen et al [52], who deposited zinc oxide nanocrystal films at rates of 500 nm in 30 s through hypersonic impaction and then infilled interparticle spaces with alumina through atomic layer deposition. The alumina matrix effectively removed trap states on the ZnO nanocrystal surfaces, resulting in very high conductivities of the ZnO nanocrystal films with mobilities up to 3 cm 2 /V s.…”
Section: Hybrid Materialsmentioning
confidence: 98%